Biological characteristics of Megacarpaea gigantea Regel fruits and their use in traditional medicine of Uzbekistan - Khamraeva, Dilovar T.; Rakhimova, Nargiza K.; Bussmann, Rainer W.; Halkuzieva , Mokhira A. (Ethnobotany Research and Applications, 2026)
Background: This article presents data on some biological, morphological, and anatomical features of the fruits of the valuable medicinal and honey plant Megacarpaea gigantea and their use in traditional medicine in Uzbekistan. Methods: Standard methods were used to study the germination of Megacarpaea gigantea seeds in laboratory conditions. A written questionnaire was used to collect ethnobotanical data. The local population was surveyed with the consent of the respondents. Interviews were conducted in accordance with the Code of Ethics established by the International Society of Ethnobiology (ISE Code of Ethics, 2006). Results: Due to the presence of fatty acids and other biologically active substances, Megacarpaea gigantea seeds are used internally as a medicinal remedy for kidney and gallbladder ailments, a fact that has been observed by local populations and tabibs over a long period of historical use. An analysis of herbarium specimens included in the electronic database of the National Herbarium of Uzbekistan, Institute of Botany, Academy of Sciences of the Republic of Uzbekistan, has identified the distribution areas of Megacarpaea gigantea in Uzbekistan (mountainous areas of Kashkadarya, Surkhandarya, Samarkand, Jizzakh, and Tashkent regions). The species is most found in the Samarkand and Kashkadarya regions, where the fruits are primarily collected by locals for ethnobotanical purposes. Three Megacarpaea gigantea seed samples, tested in laboratory conditions, failed to germinate due to pericarp sclerifications and high temperatures. A germination analysis of seeds in small containers sown in autumn and spring revealed significantly higher germination rates (up to 82-87%) in autumn, especially in clean sand. This is because the seeds sown in the autumn were subjected to natural stratification, their germination was at a satisfactory level, and with subsequent introduction work, Megacarpaea gigantea can be successfully grown based on the identified biological characteristics of the seeds. Conclusions: The medicinal properties of Megacarpaea gigantea have been identified, and a seed germination experiment was conducted in laboratory conditions and small containers with a closed root system. The mucilaginous layer of the exotesta of the spermoderm plays a role in seed adhesion to the soil and accumulates moisture for embryo germination. The fatty oils in the myrosin cells of the embryo are adaptive features for its full growth and development in arid conditions and have medicinal properties when consumed orally for gallstones and kidney stones due to their content of various beneficial fatty acids. Keywords: Megacarpaea gigantea, fruit, seed, seed germination, morpho-anatomical structure, traditional medicine.